Technology-Enabled and Universally Designed Assessment: Considering Access in Measuring the Achievement of Students with Disabilities—A Foundation for Research - Almond, Patricia; Winter, Phoebe; Cameto, Renée; Russell, Michael; Sato, Edynn; Clarke-Midura, Jody; Torres, Chloe; Haertel, Geneva; Dolan, Robert; Beddow, Peter; Lazarus, Sheryl (The Journal of Technology, Learning and Assessment, 2010)
This paper represents one outcome from the Invitational Research Symposium on Technology-Enabled and Universally Designed Assessments, which examined technology-enabled assessments (TEA) and universal design (UD) as they relate to students with disabilities (SWD). It was developed to stimulate research into TEAs designed to make tests appropriate for the full range of the student population through enhanced accessibility. Four themes are explored: (a) a construct-centered approach to developing accessible assessments; (b) how technology and UD can provide access to targeted knowledge, skills, and abilities by embedding access and interactive features directly into systems that deliver TEAs; (c) the possibility of incorporating scaffolding directly into innovative assessment items; and (d) the importance of investigating the validity of inferences from TEAs that incorporate accessibility features designed to maximize validity. Through the paper, symposium participants and contributing authors share their understanding of issues and offer insights to researchers who conduct studies on the design, development, and validation of technology-enabled and universally designed assessments that include SWD. The paper proposes a focused research agenda and makes it clear that a principled program of research is needed to properly develop and use technology-enabled and universally designed educational assessments that encourage the inclusion of SWD. As research progresses, TEAs need to improve how they assess studentsâ understanding of complex academic content and how they provide equitable access to all students including SWD.